ANALISIS STRATEGI PENINGKATAN PENERIMAAN PAJAK BUMI DAN BANGUNAN SEKTOR PERDESAAN DAN PERKOTAANPADA BADAN PENDAPATAN DAERAH KOTA PEKANBARU - Mega Pratiwi; Evi Zubaidah (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
This study aims to determine the Strategy Increasing Land Revenue Tax Rural and Urban Sector in Pekanbaru City Revenue Board. The strategy research indicators used include different competencies, scope, resourcedistribusi. Research method used is quantitative method that is by interview and interact with people in place of research. This research is categorized as a descriptive research that prioritized the questionnaire as a means of collecting data and collected data then used as the main raw material to analyze. The empirical condition of objectivity of the existence of the researcher’s objectives at the location under study.The sampling technique used in this research is using census technique method or saturated sample. The types and techniques of data collection used consisted of primary data collected by questionnaire, interview and documentation techniques and secondary data collected using obsevation techniques.While the data analysis technique used is to use the frequency tool. This study aims to analyze the strategy of increasing the receipt of tax on the earth and building the rural and urban sector in the city’s revenue agency Pekanbaru. Because the strategy is very importand to see how far the taxes of the earth and buildings can be realized through the strategy.Based on this analysis technique, the researcher concludes that the Analysis of Increasing Strategy of Increasing Land and Building Tax of Rural and Urban Sector InPekanbaru City Revenue Board is in the accomplished category.